Automated left ventricular capture management. - Crossley GH; Mead H; Kleckner K; Sheldon T; Davenport L; Harsch MR; Parikh P; Ramza B; Fishel R; Bailey JR (Pacing & Clinical Electrophysiology, 2007)
BACKGROUND: The stimulation thresholds of left ventricular (LV) leads tend to be less reliable than conventional leads. Cardiac resynchronization therapy (CRT) requires continuous capture of both ventricles. OBJECTIVE: The purpose of this study is to evaluate a novel algorithm for the automatic measurement of the stimulation threshold of LV leads in cardiac resynchronization systems. METHODS: We enrolled 134 patients from 18 centers who had existing CRT-D systems. Software capable of automatically executing LV threshold measurements was downloaded into the random access memory (RAM) of the device. The threshold was measured by pacing in the left ventricle and analyzing the interventricular conduction sensed in the right ventricle. Automatic LV threshold measurements were collected and compared with manual LV threshold tests at each follow-up visit and using a Holter monitor system that recorded both the surface electrocardiograph (ECG) and continuous telemetry from the device. RESULTS: The proportion of Left Ventricular Capture Management (LVCM) in-office threshold tests within one programming step of the manual threshold test was 99.7% (306/307) with a two-sided 95% confidence interval of (98.2%, 100.0%). The algorithm measured the threshold successfully in 96% and 97% of patients after 1 and 3 months respectively. Holter monitor analysis in a subset of patients revealed accurate performance of the algorithm. CONCLUSION: This study demonstrated that the LVCM algorithm is safe, accurate, and highly reliable. LVCM worked with different types of leads and different lead locations. LVCM was demonstrated to be clinically equivalent to the manual LV threshold test. LVCM offers automatic measurement, output adaptation, and trends of the LV threshold and should result in improved ability to maintain LV capture without sacrificing device longevity.